2012
DOI: 10.1007/s00441-012-1349-0
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of the neuropeptide PACAP in diabetic retinopathy

Abstract: Pituitary adenylate cyclase activating polypeptide (PACAP) is a neuropeptide with highly potent neurotrophic and neuroprotective effects. PACAP and its receptors occur in the retina and PACAP has been applied in animal models of metabolic retinal disorders to reduce structural and functional damage. Furthermore, PACAP has been implicated as a potential anti-diabetic peptide. Our aim has been to investigate, by using a complex morphological, immunochemical and molecular biological approach, whether PACAP attenu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 38 publications
4
45
0
Order By: Relevance
“…In a rat model of streptozotocin-induced diabetic retinopathy, early signs do not include overall changes in thickness of retinal layers, but the decrease in the number of ganglion cells and the upregulation of GFAP as a sign of Müller glial cell activation, can be observed. These changes were counteracted by three times 100 pmol/5 μl intravitreal PACAP administration [ 92 ]. Furthermore, the degeneration of the photoreceptor outer segments and terminals was attenuated in PACAP-treated rats.…”
Section: Diabetic Retinopathy In the Retinamentioning
confidence: 91%
“…In a rat model of streptozotocin-induced diabetic retinopathy, early signs do not include overall changes in thickness of retinal layers, but the decrease in the number of ganglion cells and the upregulation of GFAP as a sign of Müller glial cell activation, can be observed. These changes were counteracted by three times 100 pmol/5 μl intravitreal PACAP administration [ 92 ]. Furthermore, the degeneration of the photoreceptor outer segments and terminals was attenuated in PACAP-treated rats.…”
Section: Diabetic Retinopathy In the Retinamentioning
confidence: 91%
“…Studies in animal models have revealed some cellular components of diabetic retinal neuropathy. In diabetic rodents for example, photoreceptor death [13], [14], reduced expression of presynaptic photoreceptor proteins [15], abnormalities in horizontal and bipolar cell synaptic terminals [13], [16] and dendritic remodeling of RGCs [17] were observed.…”
Section: Introductionmentioning
confidence: 99%
“…TH is the rate-limiting biosynthetic enzyme for dopamine synthesis. Therefore, the TH protein level is a marker of dopaminergic amacrine cells in the retina [1,25,31]. Several studies showed decreased TH protein levels in the diabetic retinas, reflecting reductions in the density of dopaminergic amacrine cells [1,[31][32][33].…”
Section: Discussionmentioning
confidence: 99%